Improving The Students Science Process Skills through 5E Based on Students' Worksheets - Hidayatussakinah, Hidayatussakinah (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This research aims to determine the improvement of students' science process skills through 5E-based student worksheets (STUDENTS’ WORKSHEET) and to observe the interaction between science process skills and 5E-based students’ worksheets. This is a quasi-experimental study with a non-equivalent pretest-posttest control group design. The research was conducted from July to June 2022. The research population was all seventh-grade students of SMP Muhammadiyah Aimas, while the research sample consisted of two classes, namely VII A and VII B, taken using purposive sampling technique. The instruments used for data collection were the learning objectives, syllabus, lesson plans, 5E-based students’ worksheet, science process skills observation sheets, and test items on science process skills. The data analysis techniques used were validity, reliability, homogeneity, normality tests, and hypothesis testing using ANCOVA. The results showed that the research instruments were valid and reliable, and the data was homogenous and normally distributed. The hypothesis testing results showed that there was an improvement in students' science process skills through 5E-based students’ worksheet, and there was an interaction between science process skills and 5E-based students’ worksheet.